Penerapan CRM Sebagai Upaya Meningkatkan Kepuasan dan Loyalitas Pelanggan Pada Arya Wedding Decoration - Nur Ayu Lestari Arya; Irianto Irianto; Andrinata Andrinata (J-Com (Journal of Computer), 2022)
Abstract: Arya Wedding Decoration Sei Alim Ulu Village is a work that is engaged in services that lead to organizing an event or event, which can make it easier for customers or clients who order an event package to Arya Wedding Decoration to be held professionally with maximum results than done by the client. Arya Wedding Decoration in its implementation in organizing events consists of a team in the success of an event. The Arya Wedding Decoration Sei Alim Ulu Village in its implementation experienced several problems, namely the limited promotional media, namely only using social media applications, as well as the limited efforts to retain clients and find new clients in order to increase the existence of the Arya Wedding Decoration Sei Alim Ulu Village party. The problems that have been described underlie the need for a very popular technology whose presence has various features to know client opinions, event package promos, package ratings, event package testimonials, package orders and the convenience of contacting the Makeup and Decoration party because it is supported by an application that is directly connected to the Arya Wedding Decoration Sei Alim Ulu Village via live chat.            Keywords: CRM, wedding organizer, PHP and MySQL  Abstrak: Arya Wedding Decoration Desa Sei Alim Ulu merupakan  pekerjaan  yang  bergerak  dibidang  jasa  yang  mengarah  kepada  mengorganisasikan  suatu  kegiatan  acara  atau   event,  yang  dapat  memudahkan  pelanggan  atau  klien  yang  memesan  sebuah  paket   event   ke  pihak   Arya Wedding Decoration guna  diselenggarakan  secara  professional  dengan  hasil  yang  lebih  maksimal  dari  pada  dikerjakan  sendiri  oleh  klien.  Pihak  Arya Wedding Decoration pada  implementasinya  dalam  menyelenggarakan  event  terdiri  dari  sebuah  tim  dalam  menyukseskan  sebuah  event. Pihak Arya Wedding Decoration Desa Sei Alim Ulu dalam  implementasinya  mengalami  beberapa  permasalahan yaitu  terbatasnya  media  promosi  yaitu  hanya  menggunakan  aplikasi  sosial  media,  serta  terbatasnya  usaha mempertahankan  klien  dan   mencari  klien  baru  guna  meningkatkan  eksistensi  dari  pihak  Arya Wedding Decoration Desa Sei Alim Ulu. Permasalahan  yang  telah  diuraikan,  mendasari  perlunya  teknologi  yang   sangat  popular  kehadirannya  yang  memiliki  beragam  fitur  mengetahui pendapat  klien,  promo  paket  event,  rating  paket, testimoni  paket  event, pemesanan  paket  dan  kemudahan   menghubungi  pihak  Tata  Rias  dan Dekorasi  karena  sudah  didukung  dengan  aplikasi  yang  langsung  terhubung  dengan  pihak  Arya Wedding Decoration Desa Sei Alim Ulu  melalui   live  chat. Kata kunci: CRM, wedding  organizer,  PHP  dan MySQL.